1988
DOI: 10.1007/bf01870949
|View full text |Cite
|
Sign up to set email alerts
|

Voltage- and time dependence of apical membrane conductance during current clamp inNecturus gallbladder epithelium

Abstract: The effects of short (1 sec) and long (1 min) transepithelial current clamps on membrane voltages and resistances of Necturus gallbladder were investigated. Transepithelial and cell membrane current-voltage relationships determined from 1-sec clamps revealed that: a) depolarization of the apical membrane voltage (Vmc) results in a marked decrease in apical membrane fractional resistance (fRa), whereas hyperpolarization of Vmc results in either no change in fRa or a small increase, and b) the voltage-dependent … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
24
0

Year Published

1990
1990
1999
1999

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(26 citation statements)
references
References 31 publications
2
24
0
Order By: Relevance
“…The resulting voltage deflections (measured at 800 ms from the onset of the pulse) were corrected for series solution resistances and used to calculate transepithelial resistance (R,) and the apparent ratio of cell membrane resistances (R JR b = AVmc /AV~) (see Stoddard and Reuss, 1988b). Transepithelial voltage (Vm~), cell membrane voltages (V,,~ and V,), and differential ion-sensitive electrode voltages (Vio .…”
Section: Electrical Measurementsmentioning
confidence: 99%
See 1 more Smart Citation
“…The resulting voltage deflections (measured at 800 ms from the onset of the pulse) were corrected for series solution resistances and used to calculate transepithelial resistance (R,) and the apparent ratio of cell membrane resistances (R JR b = AVmc /AV~) (see Stoddard and Reuss, 1988b). Transepithelial voltage (Vm~), cell membrane voltages (V,,~ and V,), and differential ion-sensitive electrode voltages (Vio .…”
Section: Electrical Measurementsmentioning
confidence: 99%
“…Intracellular microelectrode (Stoddard and Reuss, 1988b) and patch-clamp studies (Segal and Reuss, 1990a, b) suggest the existence of at least two types of apical K ÷ conductances, one of which is a maxi K + channel gated by membrane depolarization and by elevation of [Ca2÷]i . This pathway can be almost totally blocked by TEA ÷.…”
Section: Isosmotic Luminal Ion Replacements In Unstimulated Tissuesmentioning
confidence: 99%
“…[n a separate set of studies, G. was estimated as a function of Vm, using 1-s transepithelial current clamps in the range _+ 300 #A/cm 2 (Stoddard and Reuss, 1988b (Stoddard and Reuss, 1988a). Recent work has revealed that depolarizing Vm, decreases Ra (Garcia-Diaz et ai., 1983;Stoddard and Reuss, 1988b).…”
Section: Microelectrode Experimentsmentioning
confidence: 99%
“…Recent work has revealed that depolarizing Vm, decreases Ra (Garcia-Diaz et ai., 1983;Stoddard and Reuss, 1988b). In the Appendix, we refine the procedure for estimating RJRb from AV,,~/AV~, measurements, accounting for voltage-induced changes in Ga and E a.…”
Section: Microelectrode Experimentsmentioning
confidence: 99%
See 1 more Smart Citation